The profitability of islamic banks and voluntary disclosure: Empirical insights from Yemen - Eissa A. Al-Homaidi; Mosab I. Tabash; Anwar Ahmad (Cogent Economics & Finance, 2020)
This study aims to empirically examine the relationship between the extent of voluntary disclosure level and profitability of Yemeni Islamic banks. This article adopted a self-constructed disclosure index, composed of 266 items, to measure the level of voluntary disclosure information and its association with the profitability of 30 annual reports of Yemeni Islamic banks, over a ten-year reporting period from 2005 up to 2014. The results with regard to return on assets (ROA) show that background about the Islamic bank, corporate governance information, corporate social disclosure, bank size, and bank age have a negative and significant relationship with return on assets. Concerning return on equity (ROE), the outcomes reveal that background about the Islamic bank, financial ratios, corporate governance information, corporate social disclosure, zakat information, and bank size have a negative and significant effect with return on equity. With respect to profit after tax (PAT), the results indicate that background about the Islamic bank, corporate social disclosure, and bank age has a negative and significant effect with profit after tax. The research mentions that regulatory bodies and managers should develop a guideline for disclosure of information to enhance the relationship between disclosure and profitability among Yemeni Islamic banks, leading to reasonable economic decision-making. This article provides important insights into the largely unexplored voluntary publication of Islamic banks ' annual reports in Yemen. The research also represents the first empirical inquiry into the correlation in the context of Yemen between the rate of voluntary disclosures and the attributes of profitability.
Keywords: 330; Islamic banks; voluntary disclosure; profitability; panel data; Yemen